PEMBERDAYAAN WANITA DALAM PENINGKATAN EKONOMI (STUDI PADA INDUSTRI RUMAHAN BANK SAMPAH DALANG COLLECTION DI KOTA PEKANBARU) - Muliani, Suci; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was held in Kelurahan Rejosari Sub-district of Tenayan Raya Pekanbaru. The purpose of this research is to know the manpower in the home industry of trash Bank, know the strategy of empowering women through the home industry of trash Bank and know the socio-economic life of women workers Dallang Collection in Kelurahan Rejosari Sub-district Tenayan Raya Pekanbaru. The focus topic of this research is the women Empowerment strategy through the home industry of Bank Sampah Dalang Collection. The samples in this study amounted to 44 people. The authors use quantitative methods and use census techniques. Data instruments are observations, polls and documentation. From the research conducted, the authors found that about employment in the garbage Bank industry Dalang Collection can be concluded as follows: the recruitment of manpower at the Dalang Collection was recruited directly from the management site 56.8%, The training provided by Dalang Collection is very beneficial for women workers 86.4%, the implementation of work in the Mastermind collection is divided into three types of work is 20.5% garbage cleaner, product pattern maker 6.8%, sewing products 72.7%. Research also finds the background of the economic life of women workers in the Dalang Collection is as a housewife who has no income and has undergone economic change since joining the Dalang Collection. The study also found that the Women Empowerment strategy through the home industry of Bank trash Dalang Collection is by increasing the confidence with the skill of respondents giving new product idea to the manager sometimes 50.0% and ever 43.2%, respondents conducted discussions with the maintainer about the creation of a new product 88.6%.Keywords: Empowerment, Social Economy,  Dalang Collection